Frequency-domain characterization of power distribution networks - Novak, Istvan Dr (Artech House microwave library, 2007)
Power distribution networks (PDNs) are key components in today's high-performance electronic circuitry. They ensure that circuits have a constant, stable supply of power. The complexities of designing PDNs have been dramatically reduced by frequency-domain analysis. This book examines step-by-step how electrical engineers can use frequency-domain techniques to accurately simulate, measure, and model PDNs. It guides engineers through the ins and outs of these techniques to ensure they develop the right PDN for any type of circuit. Circuit engineers gain valuable insight from the book's best practices for measuring, simulating, and modeling. Practical examples illustrate every phase in PDN development from material characterization and component design to modeling the entire network.